Relationship between Gender and Brand Loyalty: A Study with Special Reference to Soap, Noodles and Hair Oil in Nepal - Manandhar, Raju Bhai (Nepal Journal of Multidisciplinary Research, 2020)
The nature of the relationship between consumers and the brands to which they are loyal is, however, more wide-reaching than consumers’ behaviours and attitudes. Behavioral aspect of male and female may be different because of their choice and selection. Here, the main aim of this study was to identify the relationship between the gender and brand loyalty with reference to Soap, Noodles and Hair oil in Nepal. The study was conducted among the 200 student of private and public school of Kathmandu valley. The simple random sampling technique was used to select the students. Chi-Square Test was used to identify the relationship between the male and females to brand loyalty. The result indicates that there was significant association in brand loyalty of male and female in noodles whereas there was no significant association in brand loyalty in soap and hair oil. The future researcher can explore the factors affecting the brand loyalty of male and female.